Pelatihan Manajemen Pementasan pada Siswa Sekolah Indonesia Kuala Lumpur untuk Meningkatkan Kemampuan Penciptaan Pagelaran Pementasan Seni Pertunjukan - Indar Sabri; Trisakti, Trisakti; Eko Wahyuni Rahayu; Karoso, Subiyanto; Syaiful Qadar Basri (Yayasan Literasi Sains Indonesia, 2024)
The main role of education for the younger generation abroad is to promote and preserve the nation's cultural heritage in the context of Malaysian society. The Performance Management Training Activity for Indonesian School Kuala Lumpur (SIKL) Students aims to improve students' ability to create performing arts performances, as a solution to the less than optimal management of performing arts at the school. This PKM activity is expected to be able to bridge the needs of traditional arts in Malaysia as a means of introducing traditional arts to be promoted in Malaysia. The main objectives of this activity include training in performance management, designing performances with participants as a production team, and implementing art performances with students as a production team. The training was conducted through workshop, mentoring, project, and empowerment methods with a micro approach, which emphasized structured tasks and grouping of students for performance preparation. As a result, students were able to form a production team, work together according to their respective tasks and functions, and successfully organize the performance. However, similar activities with more interesting and effective packaging are still needed to improve the ability of SIKL students in the future.